How did the Beatles impact cultural movement on different generations? - Coman, Claudiu; Meseșan-Schmitz, Luiza; Dobrescu, Ada; Bătrânu-Pințea, Vlad (Frontiers in Communication, 2025)
IntroductionThis study aims to identify the characteristics of the new generations of Beatles fans who are engaged in online fandoms and to explore how the Beatles continue to have an impact despite the band does no longer exist. To address these objectives, the study answers to the following research questions: Does the perception of the Beatles’ impact at a personal level differ between generations of fans? If so, in what ways does the Beatles’ influence manifest in the younger generation of fans and how does the new generation of Beatles fans define themselves?MethodsIn order to conduct the study, a mixed method design was used, specifically the preliminary quantitative input variant. In the first stage we collected data to identify whether there are differences in perceptions among generations about the impact of the Beatles through an online questionnaire, with closed and open-ended questions. The population was selected non-probabilistic and comprised 788 persons who listen to the Beatles and are members of Beatles fan communities on Facebook. In the second stage, we administered an online questionnaire with open-ended questions and analogy exercises to 23 persons from the same communities, to obtain more in-depth information about the new generation of Beatles fans (aged 18–35).ResultsQuantitative data illustrate that the new generation of fans is less influenced by the Beatles. When this happens, there are two areas where this influence is more substantial: personal development and social interactions. The main elements through the identification take place with the band are lyrics from the late period of the Beatles, with a more profound message and a philosophy of life. Through analogy exercises, qualitative data reflects elements of the social identity of Beatles’ fans. Symbols like animals, plants, and instruments indicate who they are in terms of the groups.DiscussionThe findings extended our understanding of how the Beatles impact the new generation of fans and provide new insights from their social identity, which could serve as a foundation for future research, for scholar interested in exploring the identity of band music fans.